Respuesta :

Answer:

x = - 1, x = [tex]\frac{1}{8}[/tex]

Step-by-step explanation:

Given

8x² + 7x - 1 = 0 ← in standard form

Consider the factors of the product of the x² term and the constant term which sum to give the coefficient of the x- term

product = 8 × - 1 = - 8 and sum = + 7

The factors are + 8 and - 1

Use these factors to split the x- term

8x² + 8x - x - 1 = 0 ( factor the first/second and third/fourth terms )

8x(x + 1) - 1(x + 1) = 0 ← factor out (x + 1) from each term

(x + 1)(8x - 1) = 0

Equate each factor to zero and solve for x

x + 1 = 0 ⇒ x = - 1

8x - 1 = 0 ⇒ 8x = 1 ⇒ x = [tex]\frac{1}{8}[/tex]

Answer:

x

=

1

8

,

1

x=1/8,-1 I solved using  the quadratic formula

Step-by-step explanation:

ACCESS MORE